Neural Regulation of Innate Immunity in Inflammatory Skin Diseases - Xiaobao Huang; Fengxian Li; Fang Wang (Pharmaceuticals, 2023)
As the largest barrier organ of the body, the skin is highly innervated by peripheral sensory neurons. The major function of these sensory neurons is to transmit sensations of temperature, pain, and itch to elicit protective responses. Inflammatory skin diseases are triggered by the aberrant activation of immune responses. Recently, increasing evidence has shown that the skin peripheral nervous system also acts as a regulator of immune responses, particularly innate immunity, in various skin inflammatory processes. Meanwhile, immune cells in the skin can express receptors that respond to neuropeptides/neurotransmitters, leading to crosstalk between the immune system and nervous system. Herein, we highlight recent advances of such bidirectional neuroimmune interactions in certain inflammatory skin conditions.